Juridical Analysis Of Criminal Acts Of Narcotics Dark Circulation Made A House As A Methamphetamine Factory In The Region Batam City: Research Study At BNNP Kepri - Julian Maulana Syukra; Sayid Fadhil; Erniyanti Erniyanti (LITERACY : International Scientific Journals of Social, Education, Humanities, 2024)
The illicit trafficking of drugs among young people is an action that does not match the norms and social values that apply in citizens. Deviations are intertwined if a person or group of people does not comply with the norms and values that have been in force in citizens. The trigger for the formation of drug trafficking among young people is caused by some aspects of internal aspects and external aspects. Narcotics illicit trafficking policies make homes a methamphetamine factory in the Batam City area, including its own policies Implementation of narcotics illicit trafficking, supervision of police investigators in implementing the application of narcotics illicit trafficking on narcotics illicit trafficking carried out by internal supervisors namely P4GN and BNN, so that the investigation conducted by investigators in the illicit trafficking of this narcotics is protected from unwanted deviations. Supervision efforts carried out by investigators are expected that the implementation of this policy can be felt by the community. However, in the surrender it is expected to be assisted by the external supervision of the National Police and also from the community itself. Because the perpetrators of the illicit trafficking of narcotics are victims who are in dire need of supervision, so they can return with a life that is free from narcotics, and it is very necessary to support family and community supervision in the perpetrators.